Morphological characterization of concrete aggregates by means of image analysis - León, María Patricia; Ramírez, Fernando (Revista Ingeniería de Construcción, 2010)
Properties of fresh and hardened concrete are affected by the morphological characteristics of the aggregates. However, there is not an established correlation, between the aggregate shape and the concrete properties, to be taken into account during the mix design process. Conventional aggregate shape measurement methods are subjective, and that is why image analysis has been recently used to determine the morphological characteristics of particles. In this study, the morphological characteristics of coarse aggregates from two different sources are determined using both, conventional methods and image analysis by means of Fourier descriptors. Mechanical properties of concrete prepared with coarse aggregates having different elongation indexes were evaluated. Results indicate that the aggregate shape has little influence in the concrete compressive strength and elastic modulus, while its influence in workability is significant.